1995
DOI: 10.1074/jbc.270.10.5172
|View full text |Cite
|
Sign up to set email alerts
|

A 120-kDa Alkaline Peptidase from Trypanosoma cruzi Is Involved in the Generation of a Novel Ca2+-signaling Factor for Mammalian Cells

Abstract: Trypomastigotes, the infective stages of the intracellular parasite Trypanosoma cruzi, induce rapid and repetitive cytosolic free Ca2+ transients in fibroblasts. Buffering or depletion of intracellular free Ca2+ inhibits cell entry by trypomastigotes, indicating a role for this signaling event in invasion. We show here that the majority of the Ca(2+)-signaling activity is associated with the soluble fraction of parasites disrupted by sonication. Distinct cell types from different species are responsive to this… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
127
1
2

Year Published

1996
1996
2013
2013

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 107 publications
(139 citation statements)
references
References 42 publications
9
127
1
2
Order By: Relevance
“…The fact that atrial natriuretic factor, [Argx]vasopressin and [Lys*]vasopressin were more readily cleaved when reduced suggests that access to the OP-Tb active site is probably dependent on conformation as well as size. A similar enzyme from 7: cruzi was found to be vital for the infectivity of this organism, since it clcaves and activates a cytoplasmic factor involved in a calcium signalling mechanism which mediates the entry of trypanosomes into cells (Burleigh and Andrews, 1995). While a similar function for OP-Tb is unlikely since African trypanosomes are not intracellular parasites, OP-Tb may play a role in the activation of other hormone-like peptides in 7: b. brucei.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The fact that atrial natriuretic factor, [Argx]vasopressin and [Lys*]vasopressin were more readily cleaved when reduced suggests that access to the OP-Tb active site is probably dependent on conformation as well as size. A similar enzyme from 7: cruzi was found to be vital for the infectivity of this organism, since it clcaves and activates a cytoplasmic factor involved in a calcium signalling mechanism which mediates the entry of trypanosomes into cells (Burleigh and Andrews, 1995). While a similar function for OP-Tb is unlikely since African trypanosomes are not intracellular parasites, OP-Tb may play a role in the activation of other hormone-like peptides in 7: b. brucei.…”
Section: Discussionmentioning
confidence: 99%
“…The pH profile of each enzyme against synthetic substrates was investigated by substituting assay buffer with constant-ionic-strength acetate/Mes/Tris buffers (1 00 mM acetate, 200 mM Tris, 100 mM Mes, 4 mM Na,EDTA) of pH 4.0-9.0 (Ellis and Morrison, 1982). Trypanopain-Tb hydrolysis of ['4C]gelatin at various pH values was assessed using acetate/Mes/Tris buffers as described above, with the [ ''C]gelatin prepared using [ lL1'CC]acetic anhydride as described by Cawston and Barrett (1979). The pH stability of the enzymes was determined by incubating the enzymes in acetate/Mes/Tris buffers (25 mM acetate, 50 mM Tris, 25 mM Mes, 1 mM Na,EDTA) for 1 h at 37 "C before addition of a pH-7.0 assay buffer and Z-PheArg-NHMec for trypanopain-Tb, or pH-8.0 assay buffer and ZArg-Arg-NHMec for OP-Tb.…”
Section: Methodsmentioning
confidence: 99%
“…Mobilization of Ca 2ϩ from intracellular stores has been specifically implicated, since cell loading with Ca 2ϩ chelators and Ca 2ϩ store depletion by thapsigargin effectively inhibit trypomastigote entry (7,24,31). An investigation of the T. cruzi Ca 2ϩ signaling capacity revealed that the infective trypomastigotes forms contain a soluble factor capable of triggering intracellular free Ca 2ϩ transients in several mammalian cell types and that production of this factor requires the activity of a parasite serine peptidase, OPB (4,5,6,24,31). Deletion of the T. cruzi OPB gene by targeted replacement resulted in a significant attenuation of the parasite's virulence for mice and in a 60 to 70% reduction in their ability to invade mammalian cells.…”
Section: Discussionmentioning
confidence: 99%
“…This hypothesis was reinforced when trypomastigotes, the infective T. cruzi life cycle stages, were shown to activate phospholipase C and to trigger IP 3 -mediated Ca 2ϩ release from host cell intracellular stores (24,31). Characterization of this signaling pathway revealed that a parasite serine peptidase oligopeptidase B (OPB), is required for the generation of a soluble factor that triggers intracellular free Ca 2ϩ concentration ([Ca 2ϩ ] i ) transients in mammalian cells (4)(5)(6).…”
mentioning
confidence: 99%
“…Oligopeptidases only hydrolyze peptides smaller than 30 amino acid residues and as a result have no naturally occurring inhibitors. It was proposed that the Ca 2+ agonist generated by oligopeptidase B is exported from the parasite and binds to a receptor on the surface of cells, activating phospholipase C and generating inositol phosphate, which binds to its receptor on the membrane of endoplasmic reticulum and promotes Ca 2+ release [111][112][113]. Oligopeptidase B null mutant trypomastigotes are defective in mobilizing Ca 2+ from thapsigargin-sensitive stores in mammalian cells and in establishing infection in vitro and in vivo [113].…”
Section: Oligopeptidases B (Tc Op or T Cruzi Opdb)mentioning
confidence: 99%